Data dependence results of new multi-step and S-iterative schemes for contractive-like operators - Gursoy, Faik; Karakaya, Vatan; Rhoades, Billy E. (SPRINGER INTERNATIONAL PUBLISHING AG, 2013)
In this paper, we prove that the convergence of a new iteration and S-iteration can be used to approximate the fixed points of contractive-like operators. We also prove some data dependence results for these new iteration and S-iteration schemes for contractive-like operators. Our results extend and improve some known results in the literature.
Keywords: new multi-step iteration; S-iteration; data dependence; contractive-like operator; FIXED-POINTS; APPROXIMATION; THEOREMS; Mathematics